2020
DOI: 10.1007/s40123-020-00307-0
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Chart Review on Real-World Use of Latanoprostene Bunod 0.024% in Treatment-Naïve Patients with Open-Angle Glaucoma

Abstract: Introduction: The objective of this study was to evaluate real-world effectiveness of latanoprostene bunod (LBN) ophthalmic solution 0.024% in treatment-naïve patients newly diagnosed with open-angle glaucoma (OAG) or ocular hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…The majority of the patients in both studies had advanced glaucoma and the mean number of medications was similar (3.0 vs. 3.2), so the difference in efficacy is not easily explained. The present study’s data for LBN’s real-world efficacy in patients on multiple glaucoma medications, often with surgical histories, complement those of the Okeke study, which showed that LBN was effective specifically in treatment-naive eyes with a new glaucoma diagnosis 18…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The majority of the patients in both studies had advanced glaucoma and the mean number of medications was similar (3.0 vs. 3.2), so the difference in efficacy is not easily explained. The present study’s data for LBN’s real-world efficacy in patients on multiple glaucoma medications, often with surgical histories, complement those of the Okeke study, which showed that LBN was effective specifically in treatment-naive eyes with a new glaucoma diagnosis 18…”
Section: Discussionsupporting
confidence: 63%
“…The present study's data for LBN's real-world efficacy in patients on multiple glaucoma medications, often with surgical histories, complement those of the Okeke study, which showed that LBN was effective specifically in treatment-naive eyes with a new glaucoma diagnosis. 18 LBN was well-tolerated, with a favorable safety profile, with only 8 patients (14%) reporting adverse effects and only 4 patients (7%) having LBN discontinued due to these adverse effects. Of note, there were 4 patients who were excluded from analysis because they had glaucoma surgery or laser during the study window.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is supported by studies that found LBN to have IOP-lowering effects on both naive eyes and eyes on multiple glaucoma medications. 18 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials (RCTs), such as APOLLO, JUPITER, LUNAR, VOYAGER, and CONSTELLATION, as well as a pooled study conducted by Weinreb et al, have assessed the IOP-reduction effect of LBN in patients with open-angle glaucoma (OAG) and ocular hypertension (OHT) [ 9 , 10 , 11 , 12 , 13 , 14 ]. Since the approval of LBN, retrospective studies (e.g., chart reviews) regarding its IOP-lowering effect in the real-world setting have been performed [ 15 , 16 , 17 ]. To ensure a complete understanding of LBN 0.024%, we investigated its efficacy in decreasing IOP in both the RCTs and retrospective studies.…”
Section: Introductionmentioning
confidence: 99%